PENERAPAN RADIO FREQUENCY IDENTIFICATION PADA SISTEM INFORMASI PERPUSTAKAAN SEBAGAI ALAT BANTU MAHASISWA UNIVERSITAS XYZ - Muryan Awaludin; Gerly Nasukha Pribadi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2019)
The library is part of the learning resources that must be possessed by every field of education including universities. Because with the existence of a library it is expected that students can more easily find information or knowledge through a library. With the development of technology makes people think to be able to work more effectively and efficiently. One of them is to simplify activities in the library into a system that can help the process of activities at the university. By utilizing Radio Frequency Identification (RFID) technology, libraries can cut time. So that it can accelerate and simplify existing activities. In this study applying a web-based information system and utilizing RFID technology as a tool to facilitate students and library officers. With this system, it is expected to be able to overcome the various needs of students to search for books and conduct loans and make it easier for officers to circulate books and make reports. From the results of the research that has been done, the writer poured the results of the research into the Application of RFID Technology Information System as Electronic Access at the Aerospace University Marshal Suryadarma Library.Keywords: RFID, Library, Information System